2018
DOI: 10.1021/acs.analchem.8b02216
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed SERS Detection of Soluble Cancer Protein Biomarkers with Gold–Silver Alloy Nanoboxes and Nanoyeast Single-Chain Variable Fragments

Abstract: Highly sensitive, multiplexed detection of soluble cancer protein biomarkers can facilitate early cancer screening as well as enable real-time monitoring of patients' sensitivity and resistance to therapy. Current technologies for detection of soluble cancer protein biomarkers, e.g., enzyme-linked immunosorbent assay, however, suffer from limited sensitivity, as well as the requirement of expensive monoclonal antibodies, which undergo the quality variability. Herein, we propose a sensitive, cheap, and robust s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…Cyt C (5-10 × 10 −9 m) • SERS substrates for direct SERS detection • SERS nanotags for barcoding Nanodot-decorated gold-silver alloy nanoboxes [38,39] Template-free method EF ≈ 10 6 sPD-1 (6.17 pg mL −1 ), sPDL-1 (0.68 pg mL −1 ), sEGFR (69.86 pg mL −1 )…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyt C (5-10 × 10 −9 m) • SERS substrates for direct SERS detection • SERS nanotags for barcoding Nanodot-decorated gold-silver alloy nanoboxes [38,39] Template-free method EF ≈ 10 6 sPD-1 (6.17 pg mL −1 ), sPDL-1 (0.68 pg mL −1 ), sEGFR (69.86 pg mL −1 )…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Generally, SERS-based protein detection could be performed via i) target-triggered nanoassembly assays; ii) 2D substrate-based immunoassays; [108] iii) pull-down immunoassays; [39,109] and Figure 17. Generally, SERS-based protein detection could be performed via i) target-triggered nanoassembly assays; ii) 2D substrate-based immunoassays; [108] iii) pull-down immunoassays; [39,109] and Figure 17.…”
Section: Circulating Cancer Protein Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…PD1, PDL-1 and LAG-3 whole yeast scFv and nanoyeast-scFv were produced as per the method detailed in this work (Li et al 2018). To check the specificity of NY-scFvs, we performed ELISA and found that all the target scFvs have high affinities towards the target antigen (supplementary figure S3).…”
Section: Generation Of Nanoyeast-scfvmentioning
confidence: 99%
“…These were key two features in achieving detection limits of 100 fg/mL of protein from complex biological sample. SERS PD-1: 6.17 pg/mL PD-L1: 0.68 pg/mL EGFR: 69.86 pg/mL PD-1: 0.01 -1.0 ng/mL PD-L1: 0.001 -10 ng/mL EGFR: 0.1 -1000 ng/mL (Li et al 2018) SERSac-EHD (chip) PD-1: 100 fg/mL PD-L1: 50 fg/mL LAG-3: 100fg/mL PD-1: 100 fg/mL -1ng/mL PD-L1:50 fg/mL -100pg/mL LAG-3: 100 fg/mL -1ng/mL Our work considered as they are less sensitive and require high concentrations of protein. As shown in Table 1, our method has similar sensitivity like ELISA, however, has better dynamic range with low detection limit up to 100fg/mL.…”
Section: Multiplex Immune Checkpoint Detectionmentioning
confidence: 99%